Solitary cutaneous infantile myofibroma as a hallmark of myofibromatosis: Two cases and review of the literature. Issue 3 (16th March 2022) - Braun, Mitchell; Pascual, Micah; Mully, Thaddeus; Phelps, Andrew; Prok, Lori; Shah, Sonal D.; Kohn, Lucinda L.
Abstract: Infantile myofibroma (IM) commonly presents as a benign cutaneous fibrous tumor in infancy. Although the majority of solitary IM regress without any morbidity, some cases have underlying bone or visceral involvement that can lead to both morbidity and mortality. In this report with review of the literature, we present two cases of solitary cutaneous IM with internal involvement and discuss screening cases of solitary IM with full body imaging.